2021
DOI: 10.21203/rs.3.rs-174442/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiota-Derived Inosine From Dietary Barley Leaf Supplementation Attenuates Colitis Through PPARγ Signaling Activation

Abstract: Background Ulcerative colitis is a type of chronic inflammatory bowel disease closely associated with gut microbiota dysbiosis and intestinal homeostasis dysregulation. Barley leaf (BL) has a long history of use in Traditional Chinese Medicine with potential health-promoting effects on intestinal functions. However, its mechanism of action is not yet clear. Here, we explore the potential modulating roles of gut microbial metabolites of BL to protect against colitis and elucidate the underlying molecular mecha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It could activate PPARγ pathway to increase the expression of MUC-2 so that enhance the intestine barrier function. 51 Besides, both inosine and xanthosine were involved in the purine metabolism pathway. The previous study has confirmed that intestinal barrier dysfunction was correlated with purine metabolism, and related metabolites uric acid were upregulated in the DSS group.…”
Section: Discussionmentioning
confidence: 99%
“…It could activate PPARγ pathway to increase the expression of MUC-2 so that enhance the intestine barrier function. 51 Besides, both inosine and xanthosine were involved in the purine metabolism pathway. The previous study has confirmed that intestinal barrier dysfunction was correlated with purine metabolism, and related metabolites uric acid were upregulated in the DSS group.…”
Section: Discussionmentioning
confidence: 99%
“…After another 3 h, blood was collected and centrifuged at 1000 g for 15 min. Serum was obtained, and the fluorescence intensity was measured at 485 nm (excitation wavelength) and 535 nm (emission wavelength) …”
Section: Methodsmentioning
confidence: 99%
“…Serum was obtained, and the fluorescence intensity was measured at 485 nm (excitation wavelength) and 535 nm (emission wavelength). 15 2.9. Determination of Short-Chain Fatty Acids (SCFAs) in Colonic Contents.…”
Section: Evaluations Of Clinical Symptomsmentioning
confidence: 99%